Development of Apparatus for the Instant Production of Dry Gases or Fumigants - Prabha Sharma, Vinay (Asian Journal of Chemistry, 2016)
To cope up with the demand to produce dry gases for laboratory and agricultural purposes, a modified leak-proof dry gas producer is designed which can be used in agriculture for spraying instantly prepared fumigants or dry gases.